TANGGUNG JAWAB BERSAMA DALAM PENGUATAN PENDIDIKAN KARAKTER SISWA DI SEKOLAH - Nurbaiti, Nurbaiti (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA, 2017)
Education not only serves as a medium to equip learners with knowledge but also, as a container for shaping and developing intelligent self-character. The past 15 years of thuggish action among students has been a problem that awakened the government to accommodate character education in formal education. Behavioral tendencies learners out of the values of Pancasila. Government realize that there must be Mental Revolution (GNRM) to shield them from outside influences that could threaten the Homeland. Strengthening character education of the globalization era gives emphasis on religious values, honesty, love of the homeland, and peace love. In the learning process the character education is integrated in every field of study, applicative, covering the physical aspects of emotion, social, creativity, spiritual intellectual. Implementation through personal verbal and nonverbal approaches in intra-curricular, extracurricular activities in schools.